2020
DOI: 10.3389/fcvm.2020.588761
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Preoperative Hemoglobin Levels for Long-Term Outcomes of Acute Type B Aortic Dissection Post-thoracic Endovascular Aortic Repair

Abstract: Background and Aims: There is scant information available about the prognostic value of preoperative hemoglobin (Hb) levels on the long-term outcomes of acute type B aortic dissection (ABAD) following thoracic endovascular aortic repair (TEVAR). Methods: A retrospective analysis of consecutive patients from 2010 to 2018 regarding the relationship between Hb level and long-term outcomes was conducted. The primary endpoint was all-cause mortality. Major adverse cardiovascular e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 35 publications
1
4
0
Order By: Relevance
“…In recent years, it has been enclosed that it was a prognostic marker for patients with cardiovascular diseases or undergoing cardiac surgery [ 33 35 ]. Consistent with the current study, recent studies showed that hemoglobin was not only associated with in-hospital events but also influenced long-term outcomes in ABAD patients who suffered thoracic endovascular aortic repair surgery [ 36 , 37 ]. Moreover, the elevated hemoglobin is related to abdominal aortic aneurysm diameter and reduced long-term survival in patients undergoing endovascular abdominal aortic aneurysmal repair [ 38 ].…”
Section: Discussionsupporting
confidence: 89%
“…In recent years, it has been enclosed that it was a prognostic marker for patients with cardiovascular diseases or undergoing cardiac surgery [ 33 35 ]. Consistent with the current study, recent studies showed that hemoglobin was not only associated with in-hospital events but also influenced long-term outcomes in ABAD patients who suffered thoracic endovascular aortic repair surgery [ 36 , 37 ]. Moreover, the elevated hemoglobin is related to abdominal aortic aneurysm diameter and reduced long-term survival in patients undergoing endovascular abdominal aortic aneurysmal repair [ 38 ].…”
Section: Discussionsupporting
confidence: 89%
“…[ 30 ] Low hemoglobin levels can lead to anemia. Gao Z, et al [ 31 ] have shown that patients with anemia were more likely to suffer from malnutrition, hemodilution, myocardial ischemia and renal insufficiency, and inadequate tissue oxygenation delivery caused by anemia may be an important cause of aortic dysfunction. Therefore, the concentration of hemoglobin is crucial for the prognosis of AD patients.…”
Section: Discussionmentioning
confidence: 99%
“…There are studies on Troponin in AD which suggest no relation to in-hospital mortality of AD patients (27,28). Only one study was found in our literature review about hemoglobin levels which has evaluated the pre-operative hemoglobin levels and it was conducted in Type B patients (29). We included all AD patients and found out that lower hemoglobin levels are associated with a lower survival rate (p=0.041).…”
Section: Discussionmentioning
confidence: 99%